High Power Kick: Content Analysis of the USWNT 2015 World Cup Victory on American Front Pages. (December 2018) - Bell, Travis R.; Coche, Roxane
The 2015 Fédération Internationale de Football Association (FIFA) Women's World Cup final, won by the United States women's national team (USWNT), was the most-watched soccer match (men or women) in U.S. history. This quantitative content analysis examined 491 American newspaper front pages published on July 6, 2015, the day after the USWNT win. Results discuss newspapers that placed the story on their front pages (81%) and those that didn't (19%). The significant coverage of the victory indicates a small step toward improvement of a stereotypical (lack of) media representation for female athletes. However, newspapers that omitted USWNT coverage are remnants of what scholarly literature pointed toward for years: Media put more emphasis on men's sports, regardless of level of play, than they do on women's sports.